Access to Maternal Healthcare in Indonesia: Evaluating the Impact of Government Policies on Women's Health (Indonesian Health Justice Review, 2024)
Access to maternal healthcare is a critical determinant of maternal health outcomes in Indonesia, yet disparities persist in both urban and rural areas. This study evaluates the impact of Indonesia’s government policies on maternal healthcare access, focusing on the effectiveness of initiatives aimed at reducing maternal mortality and improving maternal health services. The paper examines data from national health surveys, government policy documents, and interviews with healthcare professionals and women who have experienced maternal care. Findings indicate that while significant progress has been made, especially in urban areas, rural women continue to face challenges such as long distances to health facilities, financial barriers, and inadequate quality of care. The study suggests that government policies, such as the Healthy Indonesia Program, have helped improve access to maternal healthcare but that rural women remain underserved. The research concludes with policy recommendations to improve maternal healthcare, such as increasing the number of trained healthcare workers in rural areas, expanding transportation networks, and addressing financial barriers to care.